2011
DOI: 10.2147/ceg.s17114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular pathways associated with chromosome 1p deletions during colon carcinogenesis

Abstract: Chromosomal instability is a major pathway of sporadic colon carcinogenesis. Chromosome arm 1p appears to be one of the “hot spots” in the non-neoplastic mucosa that, when deleted, is associated with the initiation of carcinogenesis. Chromosome arm 1p contains genes associated with DNA repair, spindle checkpoint function, apoptosis, multiple microRNAs, the Wnt signaling pathway, tumor suppression, antioxidant activities, and defense against environmental toxins. Loss of 1p is dangerous since it would likely co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 621 publications
(555 reference statements)
0
13
0
Order By: Relevance
“…Previous studies based on lower resolution cytogenetic analyses of primary tumors from patients with metastatic sCRC demonstrated frequent alterations of different regions at chromosomes 1p, 7, 13q, 17p, and 18q . Herein, we identified 58 different regions in these same chromosomes that were altered preferentially in primary metastatic tumors versus primary nonmetastatic tumors.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies based on lower resolution cytogenetic analyses of primary tumors from patients with metastatic sCRC demonstrated frequent alterations of different regions at chromosomes 1p, 7, 13q, 17p, and 18q . Herein, we identified 58 different regions in these same chromosomes that were altered preferentially in primary metastatic tumors versus primary nonmetastatic tumors.…”
Section: Discussionmentioning
confidence: 76%
“…Loss of chromosome 1p is well documented in sCRC . Allelic losses of chromosome 1p have been associated with increased tumor aggressiveness and reduced patient survival .…”
Section: Discussionmentioning
confidence: 99%
“…Rad54l and Mad2l2 ), the tumor suppressor gene Trp73 , numerous apoptotic genes ( Bcl10 , Casp9 , etc), as well as multiple micro-RNAs (e.g. Mir200a , Mir200b , and Mir34-a ) (Payne et al, 2011). The same reasoning may also apply to mouse chromosome 9, which is always lost in our cell lines and that contains segments homologous to portions of human chromosome arm 3p (3p21.2–3).…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomal instability group includes cancers with polypoid or aneuploid karyotypes, and cancers which have numerous insertions or losses of chromosomal arms. Chromosomal instability results from speciic molecular alterations, gene silencing, and also result from structural defects occurred during cell cycle [21]. In some of the colorectal adenomas it was observed that the tumor progression starts with chromosome 7 ampliication.…”
Section: Genomic Instabilitymentioning
confidence: 99%